Beneficial effects of aqueous extract of stem bark of Terminalia arjuna (Roxb.), An ayurvedic drug in experimental pulmonary hypertension. (2nd February 2017) - Meghwani, Himanshu; Prabhakar, Pankaj; Mohammed, Soheb A.; Seth, Sandeep; Hote, Milind P.; Banerjee, Sanjay K.; Arava, Sudheer; Ray, Ruma; Maulik, Subir Kumar
Abstract: Ethnopharmacological relevance: The stem bark of Terminalia arjuna (Roxb.) is widely used in Ayurveda in various cardiovascular diseases. Many animal and clinical studies have validated its anti-ischemic, antihypertensive, antihypertrophic and antioxidant effects. Pulmonary hypertension (PH) is a fatal disease which causes right ventricular hypertrophy and right heart failure. Pulmonary vascular smooth muscle hypertrophy and increased oxidative stress are major pathological features of PH. As available limited therapeutic options fail to reduce the mortality associated with PH, alternative areas of therapy are worth exploring for potential drugs, which might be beneficial in PH. Aim of the study: The effect of a standardised aqueous extract of the stem bark of Terminalia arjuna (Roxb.) in preventing monocrotaline (MCT)-induced PH in rat was investigated. Materials and methods: The study was approved by Institutional Animal Ethics Committe. Male Wistar rats (150–200 g) were randomly distributed into five groups; Control, MCT (50 mg/kg subcutaneously once), sildenafil (175 µg/kg/day three days after MCT for 25 days), and Arjuna extract (TA125 and TA250 mg/kg/day orally after MCT for 25 days). PH was confirmed by right ventricular weight to left ventricular plus septum weight (Fulton index), right ventricular systolic pressure (RVSP), echocardiography, percentage medial wall thickness of pulmonary arteries (%MWT). Oxidative stress in lung was assessed by super oxide dismutase (SOD), catalase, reduced glutathione (GSH) and thiobarbituric acid reactive substance (TBARS). The protein expressions of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX-1) in lung and gene expression of Bcl2 and Bax in heart were analyzed by Western blot and RT PCR respectively. Results: MCT caused right ventricular hypertrophy (0.58±0.05 vs 0.31±0.05; P<0.001 vs. control) and increase in RVSP (33.5±1.5 vs 22.3±4.7 mm of Hg; P<0.001). Both sildenafil and Arjuna prevented hypertrophy and RVSP. Pulmonary artery acceleration time to ejection time ratio in echocardiography was decreased in PH rats (0.49±0.05 vs 0.32±0.06; P<0.001) which was prevented by sildenafil (0.44±0.06; P<0.01) and TA250 (0.45±0.06; P<0.01). % MWT of pulmonary arteries was increased in PH and was prevented by TA250. Increase in TBARS (132.7±18.4 vs 18.8±1.6 nmol/mg protein; P<0.001) and decrease in SOD (58.4±14.1 vs 117.4±26.9 U/mg protein; P<0.001) and catalase (0.30±0.05 vs 0.75±0.31 U/mg protein; P<0.001) were observed in lung tissue of PH rats, which were prevented by sildenafil and both the doses of Arjuna extract. Protein expression of NOX1 was significantly increased in lung and gene expression of Bcl2/Bax ratio was significantly decreased in right ventricle in MCT-induced PH, both were significantly prevented by Arjuna and sildenafil. Conclusions: Aqueous extract of Terminalia arjuna prevented MCT-induced pulmonary hypertension which may be attributed to its antioxidant as well as its effects on pulmonary arteriolar wall thickening. Graphical abstract: